2020
DOI: 10.2147/copd.s234418
|View full text |Cite
|
Sign up to set email alerts
|

<p>Development and Pretesting of a New Functional-Based Health Literacy Measurement Tool for Chronic Obstructive Pulmonary Disease (COPD) and Asthma Management</p>

Abstract: Background: Health literacy (HL) is a person's ability to practically apply a wide range of cognitive and non-cognitive skills in health-related decisions. HL includes five domains: navigate/ access, understand, communicate, evaluate, and use of health information and services. Currently, no tool accurately captures and measures HL in adult patients with asthma and COPD, while utilizing all 5-HL domains. Objective: Develop a comprehensive functional-based measurement tool for adult asthma and/or COPD patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…and one research assistant with experience in qualitative research analysis used NVivo software (QSR International, version 12) to code the data using thematic analysis. Details of the content analysis method [64-66] applied in this study are reported in our other publications [59,60]. Content analysis helped to identify participants' viewpoints about the role of beliefs and perceptions as well as the system-related factors relevant to accessing and using information and services for their disease self-management practices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…and one research assistant with experience in qualitative research analysis used NVivo software (QSR International, version 12) to code the data using thematic analysis. Details of the content analysis method [64-66] applied in this study are reported in our other publications [59,60]. Content analysis helped to identify participants' viewpoints about the role of beliefs and perceptions as well as the system-related factors relevant to accessing and using information and services for their disease self-management practices.…”
Section: Discussionmentioning
confidence: 99%
“…We also identi ed one's willingness and motivation (according to the health promotion concepts) to engage in self-management of their chronic disease as crucial factors to be considered. Finally, we conceptualized HL in a way to explain a structurally health literate competent care system, "a system that adopts HL as an organizational value strategy in its care model" [50,60,72,78]. Such a care system should not only provide equal opportunity to all community members in accessing the needed health information and services, but also empower patients with skills necessary to navigate the system and obtain the care they need to improve their health outcomes [89,90].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As HL is a rapidly evolving and expanding concept [49,50], there has been a call-to-action to develop appropriate frameworks to comprehensively measure its core components. Several models have been reported in the literature describing HL as a multidimensional construct that improves an individual's skills related to accessing, understanding and using health information to make informed decisions about one's health [51][52][53]. For instance, McCormack et al [54,55] developed a model that presents HL as an individual-level attribute that is affected by predisposing factors or socio-environmental aspects of the target population (e.g., culture and beliefs).…”
Section: Introductionmentioning
confidence: 99%